Electrochemical sensor for determination of hydroxylamine using functionalized Fe3O4 nanoparticles and graphene oxide modified screen-printed electrode - Hamed Tashakkorian (International Association of Physical Chemists (IAPC), 2021)
A simple strategy for determination of hydroxylamine based on Fe3O4 nanoparticles functionnalized by [2-(4-((3-(trimethoxysilyl)propylthio)methyl)1-H1,2,3-triazol-1-yl)aceticacid] (FNPs) and graphene oxide (GO) modified screen-printed electrode (SPE), denoted as (Fe3O4 FNPs/GO/SPE), is reported. The electrochemical behavior of hydroxylamine was investigated at Fe3O4FNPs/GO/SPE by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometry (CHA) techniques in phosphate buffer solution (pH 7.0). Fe3O4 FNPs/GO/SPE as a novel electrochemical sensor exhibited catalytic activity toward the oxidation of hydroxylamine. The potential of hydroxylamine oxidation was shifted to more negative potentials, and its oxidation peak current increased on the modified electrode, also indicating that under these conditions, the electrochemical process is irreversible. The electrocatalytic current of hydroxylamine showed a good relationship in the concentration range of 0.05–700.0 μM, with a detection limit of 10.0 nM. The proposed electrode was applied for the determination of hydroxylamine in water samples, too.